Impacts of Perceived Utility Value, Self-esteem. Perceived Organizational Support on Teachers’ Career Choice Satisfaction (Global Business Management Review (GBMR), 2021)
Recruiting and retaining prospective English teachers are two major issues worldwide because they involve career choice satisfaction and future life. Hence, the purpose of this study is to investigate factors influencing career choice satisfaction among English language trainee teachers from the Institute of Teacher Education in Malaysia. Social Cognitive Theory (SCT) is used to explain the study. This study includes personal utility value, self-esteem, and perceived organizational support as the variables that affect career choice satisfaction. Data were collected from 127 trainee teachers who enrolled in the Teaching English as Second Language (TESL) course at the Institute of Teacher Education in Malaysia using a self-administered questionnaire. The study’s hypotheses were tested using SmartPLS. This data set were analysed using reflective-formative second-order construct because perceived utility value consists of two dimensions. The results show that personal utility value, self-esteem, and perceived organizational support have a positive effect on career choice satisfaction. The results offer useful information to the related education organizations and institutions to develop and improve strategic plans in recruiting, retaining and improving the teaching workforce.